Diffusion in Social Networks: Experimental Evidence on Information Sharing vs Persuasion - Marcel Fafchamps; Asad Islam; Debayan Pakrashi; Denni Tommasi (Institute of Labor Economics (IZA), 2024)
We conduct a clustered randomized controlled trial across 180 villages in Uttar Pradesh, India, to promote the take-up of a savings commitment product newly introduced to our study population. A random subset of participants was targeted through our promotional campaign to test whether the product's diffusion among untargeted participants operates primarily through information sharing or through persuasion by incentivized target participants. If social learning is the main channel of diffusion, we would expect higher sign-up and take-up rates in information villages compared to persuasion villages. Conversely, if persuasion is the primary channel, sign-up and take-up rates should be higher in persuasion villages. Our findings consistently favor the persuasion channel, as sign-up and take-up rates were higher in the persuasion treatment, even without increased financial literacy or knowledge about the product. Information alone had a negligible impact on take-up, while the combined treatment achieved the highest sign-up and conversion rates, suggesting that information complements persuasion by enhancing its effectiveness. These results highlight the importance of incentivized persuasion in promoting product take-up and suggest that, in certain contexts, direct information-sharing may be less effective than previously assumed.
Keywords: O16; D14; G21; 330; diffusion; social networks; savings; financial inclusion; information; persuasion